2020
DOI: 10.1186/s40560-020-00483-y
|View full text |Cite
|
Sign up to set email alerts
|

Thromboembolic disease in COVID-19 patients: A brief narrative review

Abstract: Corona virus 2 (SARS-CoV2/ Severe Acute Respiratory Syndrome Corona Virus 2) infection has emerged as a global health crisis. Incidence of thromboembolic disease is reported to be high in SARS-CoV2 disease and is seen in a multitude of organ systems ranging from cutaneous thrombosis to pulmonary embolism, stroke or coronary thrombosis sometimes with catastrophic outcomes. Evidence points towards a key role of thromboembolism, hypercoagulability and over production of proinflammatory cytokines mimicking a “cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
75
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 109 publications
0
75
0
2
Order By: Relevance
“…14 However, the optimal approach to management of anticoagulation in patients with COVID-19 is not certain. 15 Of note, our patient had reportedly received prophylactic low molecular weight heparin at an outside medical facility prior to presentation to our hospital. The failure of thromboprophylaxis in COVID-19 patients has been described in the literature previously and may be due to multiple prothrombotic factors.…”
Section: Discussionmentioning
confidence: 90%
“…14 However, the optimal approach to management of anticoagulation in patients with COVID-19 is not certain. 15 Of note, our patient had reportedly received prophylactic low molecular weight heparin at an outside medical facility prior to presentation to our hospital. The failure of thromboprophylaxis in COVID-19 patients has been described in the literature previously and may be due to multiple prothrombotic factors.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies have reported 16% to 31% of COVID-19 patients to have some form of TE/complications and higher mortality in Covid-19 patients with TE. 1 , 4 Our data from a very large sample of all-comers COVID-19 patients (including out-patients) shows a smaller prevalence of TE. This also provides more comprehensive estimates of the increased risk of worse outcomes including mortality in COVID-19 patients with TE events and underscores the need for intensive screening and thromboprophylaxis in these patients.…”
mentioning
confidence: 76%
“…Apart from respiratory complications, also neurologic impairment or kidney failure were more common in the COVID-19 cohort. It is unclear whether this finding might be explained by vasculitis and thromboembolic events, which are common in COVID-19 24 . Surprisingly, there was no difference in cardiovascular complications.…”
Section: Discussionmentioning
confidence: 99%